Lower limb compartment syndrome as a complication of robot‐assisted radical prostatectomy: the UK experience. (23rd July 2013) - Pridgeon, Simon; Bishop, Conrad V.; Adshead, Jim
<x xml:space="preserve">Abstract</x> Objective To evaluate the incidence of lower limb compartment syndrome (LLCS) in robot‐assisted radical prostatectomy (RARP) and the prevalence of risk factors in patients with LLCS. Methods Data were collected from 17 UK robotic surgery institutions for a multicentre analysis. Data were used to calculate the incidence of LLCS and the prevalence of risk factors. Results A total of 3110 RARPs were performed by 17 institutions between 2004 and 2011. There were nine cases of LLCS, giving an incidence of 0.29%. Seven of these required fasciotomy. The prevalence of risk factors was as follows: console time >4 h in 8/9 cases, early learning curve (<20 cases) in 3/9 cases; obesity (BMI >30 kg/m2) in 5/9 cases; and peripheral vascular disease in 2/9 cases. One patient with LLCS was positioned incorrectly. Conclusions The serious complication LLCS occurs in RARP but has a low incidence. Long operating times, surgical inexperience, poor patient positioning, obesity and vascular disease appear to be risk factors.